Continuous Change as a Disruptive Force: Exploring Homecare Transitions for Carers of People Living with Dementia in Scotland - Cranwell, Marianne (International Journal of Educational and Life Transitions, 2023)
Due to an ageing population and strategic moves away from institutional care, the number of informal carers supporting a person living with dementia in Scotland is set to rise. The shift toward community-based care means that informal carers are often in contact with homecare workers during a transitional period between being the primary carer and sharing care with homecare workers. As part of the findings from a larger study that focused on the experiences of co-habiting carers of a person living with dementia when homecare began, this article presents ‘continuous change as a disruptive force’ as a key concept of carers’ experiences of transition. Recognition of continuous change for carers can inform our understanding of transitional processes and ways in which homecare providers’ response to change has considerable impact on carers’ transitional experiences. Interview data were generated remotely with five participants in Scotland. Two participants completed eight interviews over a period of six months. All data was collected between June 2021 and December 2021. Data were collected by telephone, online video meeting (Teams), and in one instance by email and analysed using reflexive thematic analysis. This article focuses on disruption through change caused by dementia – including unpredictability and impermanence, and homecare providers’ lack of responsiveness the closer to crisis participants became. In conclusion, the experiences of transitions to homecare for those caring for a person living with dementia are multiple, complex, and perpetual. I recommend subsequent research into reducing liminal periods for people encountering non-normative transitions and suggest that homecare providers focus resources on providing consistent and reliable services and on training staff specifically in carer support.